2018
DOI: 10.14740/jocmr3294w
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Regarding Tonometry and the Transmission of Infectious Diseases

Abstract: Tonometry has been identified as a common method for measuring the intraocular pressure in patients. The direct contact between the tonometer and the eye may contribute to the risk of cross infection, especially of viral particles, from one patient to another. A systematic review was undertaken to address the likelihood of human immunodeficiency virus (HIV), hepatitis B virus, hepatitis C virus, and prion diseases transmission through the use of tonometers. Additionally, a comparison of the current tonometer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have reported that applanation tonometry has the potential to transmit a variety of infectious agents, including adenovirus 8 and herpes simplex virus 1, and reusable tonometer prisms could, in theory, be a mode of transmission for hepatitis B, hepatitis C, human immunodeficiency virus, and Creutzfeldt-Jakob disease. [31][32][33][34][35][36][37] A systematic review of 11 studies assessing the disinfection of Goldmann tonometers concluded that there is no definitive optimal technique or agent for the disinfection of Goldmann applanation tonometer prisms. 30,33 The AAO supports the use of diluted bleach for the disinfection of reusable tonometer tips for SARS-CoV-2 and adenovirus.…”
Section: Contact Tonometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that applanation tonometry has the potential to transmit a variety of infectious agents, including adenovirus 8 and herpes simplex virus 1, and reusable tonometer prisms could, in theory, be a mode of transmission for hepatitis B, hepatitis C, human immunodeficiency virus, and Creutzfeldt-Jakob disease. [31][32][33][34][35][36][37] A systematic review of 11 studies assessing the disinfection of Goldmann tonometers concluded that there is no definitive optimal technique or agent for the disinfection of Goldmann applanation tonometer prisms. 30,33 The AAO supports the use of diluted bleach for the disinfection of reusable tonometer tips for SARS-CoV-2 and adenovirus.…”
Section: Contact Tonometrymentioning
confidence: 99%
“…[31][32][33][34][35][36][37] A systematic review of 11 studies assessing the disinfection of Goldmann tonometers concluded that there is no definitive optimal technique or agent for the disinfection of Goldmann applanation tonometer prisms. 30,33 The AAO supports the use of diluted bleach for the disinfection of reusable tonometer tips for SARS-CoV-2 and adenovirus. If available, single use, disposable tonometer prisms provide an alternative to reusable prisms to prevent cross-contamination.…”
Section: Contact Tonometrymentioning
confidence: 99%
“…The presence of PrP Sc in dust particles, grass blades, and water reservoirs have prompted studies on peripheral routes of entry from the conjunctiva with positive results (Gough et al, 2015). Thus, the eye is a source of PrP Sc transmission, all be it at a much slower state (Atkins et al, 2018;Gnanajothy et al, 2013). This is an important question since horizontal spread of animal prions through corneal abrasions is a distinct possibility (Asthana et al, 2017).…”
Section: The Eye As a 'Window' To The Brainmentioning
confidence: 99%
“… 7 It has also been found to pose a lower risk of cross-infection. 10 Unlike the GAT which has to be used whiles mounted on a slit lamp, the NCT exists in table-top and portable forms. 9 …”
Section: Introductionmentioning
confidence: 99%